(untitled) - Instituto Monsa de Ediciones, S.A (Kali Bukit Techpark II, Singapore, 2005)
With ever-increasing numbers of savvy customers, and the growing exchange of information on destinations, hotels have discovered that they must constantly keep upgrading and improving in order to hold their appeal for discriminating travelers. The innovative designs in Hotel Design redefine the concept of what a hotel should be, from a design standpoint as well as the consumer standpoint. With thorough documentation, floor plans, the architects’ own sketches and notes, and hundreds of glowing color photos, Hotel Design is a great place to settle down for a long stay
Keywords: Hotels,Interior architecture,Hotels,Hotels; Decoration,Planning,Design and construction